IMPLEMENTASI MINDFULNESS LEARNING DALAM MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH PADA PERKALIAN DAN PEMBAGIAN PECAHAN DI MTS NEGERI PAREPARE - Nurjannah; Nurwahida; Buhaerah; Azmidar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the implementation steps of Mindfulness Learning and analyze its effectiveness in improving students’ mathematical problem-solving skills on the topic of fraction multiplication and division at MTs Negeri Parepare. The low level of problem-solving ability was identified as being caused by a lack of focus, attention, and mental engagement during learning activities. This research employed a quantitative approach with a quasi-experimental design (one-group pretest–posttest). Data were collected through observation, mathematical problem-solving tests, and documentation, then analyzed using descriptive and inferential statistics with a paired sample t-test. The results are expected to show a significant improvement in students’ mathematical problem-solving abilities after the implementation of Mindfulness Learning, as well as positive behavioral changes toward more focused, calm, and reflective learning habits.